Exploring the influence of redox and temperature variations on the attenuation of pharmaceuticals in groundwater: Insights from parallel batch reactor experiments - Alejandra Villa; Nafiseh Salehi Siavashani; Estanislao Pujades-Garnes; Nicola Montemurro; Sandra Pérez; Jan Willem Foppen; Marc Teixidó; Anna Jurado (Emerging Contaminants, 2025)
Pharmaceuticals are present in the environment from anthropogenic pollution sources, leading to groundwater contamination when reaching urban aquifers. Once in the subsurface, their fate depends on the hydrochemical processes and environmental conditions within the aquifer. In this context, this study investigates how different redox and temperature conditions affect the natural attenuation of pharmaceuticals in the subsurface. Batch experiments were conducted under oxic and suboxic (i.e., up to nitrate reduction) conditions and at two temperatures (25 °C and 35 °C). The controlled conditions achieved with parallel batch reactor systems allowed us a systematic investigation of the processes and factors involved in the fate of ten pharmaceuticals (atenolol, citalopram, climbazole, irbesartan, lamotrigine, sitagliptin, carbamazepine, metoprolol, trimethoprim, and venlafaxine), providing insights into the mechanisms governing their attenuation. The results showed that oxic conditions were highly effective in reducing pharmaceuticals concentrations, achieving up to 91 % attenuation for irbesartan, followed by citalopram (90 %), climbazole (77 %), sitagliptin (76 %) and metoprolol (75 %). Atenolol and climbazole were also attenuated regardless of redox conditions. High temperatures increased the total removal of citalopram, irbesartan, sitagliptin, and trimethoprim by 5–12 %, while slightly enhancing the sorption affinity of carbamazepine, irbesartan, and atenolol by 5 %. However, trimethoprim, carbamazepine, and lamotrigine were the most persistent compounds, with average removal rates of 6 %, 15 %, and 24 %, respectively. Overall, more than half of the targeted pharmaceuticals showed significant average removal (>60 %), highlighting the influence of the processes involved in groundwater on the natural attenuation of these compounds. Sorption seemed to be the primary process contributing to the target pharmaceuticals attenuation in oxic conditions, while biodegradation played a secondary role, particularly for atenolol and metoprolol. These findings contribute to improve our understanding of the behaviour of pharmaceuticals in aquatic environment and thus to improve management practices for better water quality.